Ethical value of cranioplasty with oppressive binder as a way of limiting life support treatments - Canabal Berlanga, Alfonso; Jara Rascón, José; Gómez Rodríguez, Rafael; Abengózar Muela, Ricardo; Ruiz Hornillos, Francisco Javier; Moreno Villares, José Manuel; de Santiago Corchado, Manuel; Viejo Llorente, L. Fernando; Abellán Salort, José Carlos; Gándara del Castillo, Álvaro (Acta Bioethica, 2015)
This article analyzes, from a critical perspective, the use of cranioplasty with oppressive binder as a method to limit life support treatment (LLST). Some authors have proposed that this active technique provokes encephalic death, allowing organ donation. Contrasting this procedure with the recommendations of the consent document about treatment of critical patients at the end of life, elaborated by the bioethics group of SEMICYUC, it is shown that the means and ends of this technique do not match with the proper actions of LLST, based on the withdrawal of life support means or in not starting them, considering such means disproportionate or extraordinary in some cases, thus avoiding the therapeutic obstinacy. The definition of LLST allows to clarify the limits in which, in a way ethically fair and with a consensus, the acts at the end of life are included in the medical goals, avoiding the suspicion that these acts may be misinterpreted as justifying an abusive extraction of organs. This article concludes that the direct provocation of encephalic death by the technique of cranioplasty with binder does not appear to fulfill the criteria proper of LLST.